Sign Changes of Kloosterman Sums with Almost Prime Moduli. II. (24th December 2016) - Xi, Ping
Abstract: We prove that the Kloosterman sum $S(1, 1;c)$ changes sign infinitely often as $c$ runs over squarefree numbers with at most 7 prime factors, which improves the previous results of Fouvry and Michel, Sivak-Fischler, Matomäki, and the author.